In-kind transfer and child development: Evidence from subsidized rice program in Indonesia - Prachi Gupta; Bihong Huang (Asian Development Bank Institute (ADBI), 2018)
In the aftermath of the Asian financial crises, the Indonesian government launched a subsidized rice program called RASKIN in 1998 to moderate the shocks of food price inflation and reduced employment to poor households. The program has been continued since then with an objective to provide food security to poor families and is currently the largest in-kind transfer in Indonesia. Using data from five rounds of the Indonesian Family Life Survey (IFLS) covering the period of 1993-2014, this paper examines the impact of RASKIN on children's health status. Using the difference-in-difference estimator, we find that children from the households that are beneficiaries of the RASKIN program show improved health status as measured by various anthropometric measures. We further investigate the long-run gains from RASKIN by tracing the health status of children aged between 0 and 5 years old in 1993 and 1997 respectively until their adolescence/adulthood. We find evidence of improved anthropometric health outcomes for these children in later years. The gains are found to be higher for children who started receiving the subsidized rice in the early years of childhood.
Keywords: I38; I12; H5; O15; Q18; 330; in-kind transfers; food consumption; child development; health; long-run impact